2021
DOI: 10.7759/cureus.14445
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pneumocystis Pneumonia in HIV Patient on Glucocorticoid

Abstract: Pneumocystis pneumonia (PCP) is an opportunistic infection caused by Pneumocystis jirovecii. PCP due to immunosuppressive drugs is rarely reported in the literature. Herein we present a case of PCP in a 49-yearold patient who presented with progressive shortness of breath, dry cough, and low-grade fever. History revealed that he was taking prednisolone daily for his hyperactive airway disease. His temperature was 99 o F, and he had bilateral crackles in the lungs with resonant wheezing. High-resolution compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Twenty-five articles were excluded due to the following reasons: no full-text ( N = 09), literature reviews ( N = 04), inappropriate intervention ( N = 03), no required data ( N = 03), and non-English ( N = 06). A total of 13 articles met the inclusion criteria for final analysis [ 3 , 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Of the 13 selected studies, nine were retrospective cohort studies [ 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 34 ], two case reports [ 31 ] and two randomized controlled trial (RCT) [ 3 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five articles were excluded due to the following reasons: no full-text ( N = 09), literature reviews ( N = 04), inappropriate intervention ( N = 03), no required data ( N = 03), and non-English ( N = 06). A total of 13 articles met the inclusion criteria for final analysis [ 3 , 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Of the 13 selected studies, nine were retrospective cohort studies [ 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 34 ], two case reports [ 31 ] and two randomized controlled trial (RCT) [ 3 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 articles met the inclusion criteria for final analysis [ 3 , 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Of the 13 selected studies, nine were retrospective cohort studies [ 8 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 34 ], two case reports [ 31 ] and two randomized controlled trial (RCT) [ 3 , 33 ]. The PRISMA flow diagram reporting the procedure of selection of studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the radiological aspects described above are typical of pulmonary infection with P. jirovecii , the existence of focal cystic lesions has been reported, with only a few studies showing cavitary lesions during PCP [ 21 , 22 ]. The definitive diagnosis of PCP is made by polymerase chain reaction (PCR) of respiratory specimens or fluorescein antibody staining [ 23 ].…”
Section: Discussionmentioning
confidence: 99%